The impact of dual- versus single-dosing and fatty food co-administration on albendazole efficacy against hookworm among children in Mayuge district, Uganda: Results from a 2x2 factorial randomised controlled trial - Eun Seok Kim; Moses Adriko; Wamboko Aidah; Kabarangira Christine Oseku; David Lokure; Kalpana Sabapathy; Emily L. Webb (Public Library of Science (PLoS), 2023)
Background Mass Drug Administration (MDA) is the main strategy for control of soil-transmitted helminth (STH) infections, with single-dose benzimidazole (albendazole or mebendazole) the principal MDA option. In Mayuge district, Uganda, an MDA programme has been in place for over fifteen years but hookworm infection remains common and there is concern that the effectiveness of single-dose albendazole as currently used for MDA may be sub-optimal. This study aims to assess the efficacy of dual- versus single-dose albendazole, with and without fatty food co-administration against hookworm, the dominant form of STHs in Mayuge district, Uganda. Methodology This was a 2x2 factorial randomised controlled trial to investigate two interventions simultaneously; 1) dual-dose versus single-dose albendazole, 2) taking albendazole with or without fatty food (200 grams of avocado eaten directly after medication). School children with hookworm infection were randomised in a 1:1:1:1 ratio to the four possible treatment groups. Three weeks after the treatment, stool samples were collected from trial participants to evaluate trial outcomes: cure rate and egg reduction rate (ERR). Principal findings A total of 225 participants were enrolled, and 222 (98.7%) seen at 3 weeks. The cure rate in the dual-dose group was 96.4% (95% CI: 90.9-99%), higher than 83.9% (95% CI: 75.7-90.2%) in the single-dose group (OR: 5.07, 95% CI:1.61-15.96, p = 0.002). The ERR was 97.6% and 94.5% in the dual-dose group and single-dose drug group, respectively (ERR difference 3.1%, 95% CI: -3.89-16.39%, p = 0.553). The cure rates among participants taking albendazole with and without avocado were 90.1% and 89.1%, respectively, with no statistical difference between the two groups (OR: 1.24, 95% CI: 0.51-3.03, p = 0.622). The ERR was 97.0% and 94.2% in the group receiving albendazole with and without avocado, respectively, and the difference in ERR between the two groups was 2.8% (95% CI -8.63-14.3%, p = 0.629). Conclusions/Significance In Ugandan school children, dual-dose albendazole improves the cure rate of hookworm compared to single-dose albendazole. However, there was no significant improvement in cure rate or egg reduction rate of hookworm with fatty-food co-administration. Dual-dose albendazole is a feasible alternative for improving drug effectiveness against hookworm infection and minimising drug resistance. Trial registration PACTR202202738940158. Author summary Mass Drug Administration (MDA) of single-dose albendazole is the main strategy for control of soil-transmitted helminth infections including hookworm, but these infections remain common in many settings where MDA has been implemented for several years. This study aimed to assess the efficacy of dual-dose versus single-dose albendazole, with and without fatty food co-administration, against hookworm infection in Mayuge district, Uganda. The study was conducted as a randomized controlled trial among school children with hookworm infection. The cure rate was found to be significantly higher in the dual-dose group compared to the single-dose group, with no significant difference in the cure rate or egg reduction rate observed between the groups that took albendazole with or without fatty food. The study suggests that dual-dose albendazole is a feasible alternative for improving drug effectiveness against hookworm infection and minimizing drug resistance. Although the study did not demonstrate any benefit with the use of avocado co-administration against hookworm infection, further exploration is warranted due to the biological rationale for improving albendazole efficacy to treat intraluminal hookworm infection.